Clinical Relevance of Blood Glucose Concentration and Hyperglycemia Management in Neurocritical Care Patients - Bilotta, Federico; Qeva, Ega; Prete, Anna; Pugliese, Francesco (Journal of Neuroanaesthesiology and Critical Care, 2019)
In patients admitted to a neurocritical care (NCC) unit, management of blood glucose concentration (BGC) is a challenging clinical task. Several studies have shown that episodes of hypo- and hyperglycemia and high BGC variability are associated with poor short- and long-term outcomes. Optimal BGC target-range and BGC management in NCC patients have dramatically evolved in the past decades and new insulin infusion and adequate nutrition protocols are now available. The aim of this narrative review is to report the state-of-the-art on clinical relevance on BGC and hyperglycemia management in NCC patients.
Keywords: acute brain injury; blood glucose concentration; insulin infusion therapy; neurocritical care